KAJIAN ASPEK TEKNIS PERIKANAN GILLNET BERBASIS EAFM (ECOSYSTEM APPROACH TO FISHERIES MANAGEMENT) DI PERAIRAN DUMAI - Sari, Ratih Purnama; Shalichaty, Shiffa Febyarandika (Universitas Teuku Umar, 2020)
The local government law regulated the management of 0 – 12 miles waters carried out by the province so that fishermen can operate their fishing gear without differentiating districts. Catch fishing was not limited to one kind of fishing gear and it caused the increasing of fishing capacity. The limited area of fishing with the distance of 2 miles from coast can caused fisheries utilization resources was not balanced. Therefore this study needed to be conducted to assess the status of development of gillnet fishing activities in Dumai waters. Data was collected by conducting interviews in the form of: fishing units, selectivity, sustainability of function and size of fishing vessel with legal documents, and modification of fishing gear. The data results based on 5 fishing technical aspects explained that the fishing utilization of gillnet still could be developed. However, the data of fishing vessel documents have to be well recorded according to the reality so that government could develop the responsible fishing activities.